Bureaucratic Reform and Abuse of Power Implicate Corruption in Public Services: A Philosophical Perspective of Law in the North Halmahera Regency Government - Elstonsius Banjo (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
Bureaucratic Reform is a process of restructuring government bureaucracy, encompassing organization, governance, legislation, human resources, supervision, accountability, and public services, as well as the mindset and cultureset (work culture) of the apparatus. In practice, bureaucratic reform has not been optimally implemented, resulting in frequent abuse of power that has implications for corruption.  The purpose of this research that is bureaucratic reform to become a necessity and a foundation for the North Halmahera Regency government apparatus, in order to successfully lay the political, legal, and economic foundations for democratic life in Indonesia. The "doctrinal research" method is used and the analysis is conducted qualitatively through an "Analytical-Critical" approach, to produce descriptive and perspective legal concepts and then create legal philosophical constructions through testing and assessment based on legal concepts, principles, and theories obtained in library-based studies as a philosophical perspective of law reflection. The research findings indicate that bureaucratic reform is essential for the North Halmahera Regency Government to prevent abuse of power, which could lead to corruption in public services. It is recommended that bureaucratic reform become a fundamental foundation for regional governance, providing a platform for philosophical of law reflection on public services, evaluation, and constructive ideas as the North Halmahera Regent enters his second year in office. It also serves as intellectual and social documentation of the dynamics of North Halmahera's journey toward an equal, just, and sustainable society.